The nanos translational control element represses translation in somatic cells by a Bearded box-like motif. - Duchow, H.K.; Brechbiel, J.L.; Chatterjee, S.; Gavis, E.R. (Developmental Biology, 2005)
Developmental control of translation is frequently mediated by regulatory elements that reside within 3' untranslated regions (3' UTRs). Two stem-loops within the nanos 3' UTR translational control element (TCE) act independently to direct translational repression of maternal nanos mRNA in the ovary or embryo. We have previously shown that the nanos TCE can also function in select somatic sites. Using an ectopic expression screen, we now identify a new site of TCE function, the dorsal pouch epithelium. Analysis of TCE mutants reveals that TCE activity in the dorsal pouch does not depend on either of the stem-loops required for maternal TCE function, but instead requires a third feature-a sequence that closely matches the Bearded box, a regulatory motif found in the 3' UTRs of several Notch pathway genes. In addition, we identify pleiohomeotic mRNA as an endogenous candidate for regulation by Bearded box-like motifs in the dorsal pouch. Together, these results suggest that the TCE has appropriated a conserved regulatory motif to expand its function to somatic tissues.